2019
DOI: 10.1073/pnas.1907447116
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus glycoprotein B variants affect viral entry, cell fusion, and genome stability

Abstract: Human cytomegalovirus (HCMV), like many other DNA viruses, can cause genome instability and activate a DNA damage response (DDR). Activation of ataxia-telangiectasia mutated (ATM), a kinase activated by DNA breaks, is a hallmark of the HCMV-induced DDR. Here we investigated the activation of caspase-2, an initiator caspase activated in response to DNA damage and supernumerary centrosomes. Of 7 HCMV strains tested, only strain AD169 activated caspase-2 in infected fibroblasts. Treatment with an ATM inhibitor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…e gB gene is highly conserved within the Herpesviridae family, and is widely used as a candidate gene in herpesvirus species identification and phylogenetic analysis [26][27][28]. Here, in this study, the nucleotide and amino acid sequences comparison demonstrated that DPOL gene sequences in different PCMV isolates are highly conserved, with no significant variation between DPOL nucleotide and amino acid sequences from different PCMV isolates.…”
Section: Discussionmentioning
confidence: 62%
“…e gB gene is highly conserved within the Herpesviridae family, and is widely used as a candidate gene in herpesvirus species identification and phylogenetic analysis [26][27][28]. Here, in this study, the nucleotide and amino acid sequences comparison demonstrated that DPOL gene sequences in different PCMV isolates are highly conserved, with no significant variation between DPOL nucleotide and amino acid sequences from different PCMV isolates.…”
Section: Discussionmentioning
confidence: 62%
“…gB1 and gB2 types are often seen in patients with transplantation and infection with human immunodeficiency virus (HIV), respectively ( Fries et al, 1994 ; Shepp et al, 1996 ). The 275Y variants of gB expressed on the AD169 strain promote fusogenicity with activation of caspase 2 and the DNA damage response since the 275D variants show less syncytium formation and an inability to trigger caspase 2 ( Tang et al, 2019 ). Whether gB genotypes are associated with cell tropism are largely elusive.…”
Section: Hcmv Structurementioning
confidence: 99%
“…However, the mechanism of entry into fibroblasts is still under discussion. Recent observations suggest that it may occur via a rapid micropinocytosis [54] or even by direct fusion with the outer plasma membrane through the fusogenic activity of gB [55].…”
Section: Genetic Determinants Of Hcmv-tropism For Human Fibroblastsmentioning
confidence: 99%
“…The discovery that HCMV uses different glycoprotein complexes for entry into endothelial cells/epithelial cells [42,43] and into fibroblasts [52] prompted us to investigate whether human antibody response to natural HCMV infection displayed different levels of neutralization potential against the infection of these two cell types. Results showed that in the convalescent phase of primary HCMV infection, the reciprocal geometric mean neutralizing antibody titer was >30-times more potent in neutralizing infection of epithelial cells/endothelial cells than that of fibroblasts [55]. The primary candidates for this differential neutralizing activity appeared to be antibodies directed against UL128L proteins, as indirectly suggested by murine and rabbit polyclonal antibodies raised against the individual components of pUL128L [44,56,57].…”
Section: Gh/gl/pul128l and Gh/gl/go Complexes: Development And Chamentioning
confidence: 99%